Избранные произведения: в 3 т. (К. Маркс, Ф. Энгельс) - Маркс Карл (1983)
Экземпляры: аб (ретроконверсия) / Инвентарный номер: 9875 / Цена: 0.95 / Сис.шифр: 87.3 / Авт.знак: М 27 / ГРНТИ: 02 / ББК: 87.3